Investigating the Effects of Language-Switching Frequency on Attentional and Executive Functioning in Proficient Bilinguals - Barbu, Cristina-Anca; Gillet, Sophie; Poncelet, Martine (Frontiers in Psychology, 2020)
Recent studies have proposed that the executive advantages associated with bilingualism may stem from language-switching frequency rather than from bilingualism per se (see, for example, Prior and Gollan, 2011). Barbu et al. (2018) showed that high-frequency switchers (HFLSs) outperformed low-frequency switchers (LFLSs) on a mental flexibility task but not on alertness or response inhibition tasks. The aim of the present study was to replicate these results as well as to compare proficient (HFLSs and LFLSs) to a control group of monolingual participants. Two groups of proficient bilingual adults (30 HFLSs and 21 LFLSs) and a group of 28 monolinguals participated in the study. The results showed superior mental flexibility skills in HFLSs compared to (LFLSs) and monolinguals; furthermore, the two latter groups showed no difference in mental flexibility skills. These results provide novel support for the hypothesis that the so-called bilingual advantage is, in fact, a result of language-switching habits.